Peningkatan Literasi Green Finance melalui Edukasi dan Proyek Siswa SMK Muhammadiyah 2 Palembang - Ummi Kalsum; Primasari Fitria; Ayu Geby Gisela Syahputri; Randy Hidayat; Arradytia Permana; Yunita Febriani (Universitas Negeri Gorontalo, 2026)
The Community Service Program (PKM) conducted at SMK Muhammadiyah 2 Palembang was designed to enhance students’ green finance literacy as part of efforts to strengthen environmentally responsible financial behavior in the school setting. The program implemented several learning activities, including seminars on green finance concepts, training on sustainable financial management, and project-based assignments in which students designed simple green finance initiatives relevant to their vocational fields. A total of 35 students from grades X and XI participated under the guidance of supervising teachers. The results of the program show a marked improvement in students’ knowledge. The average pre-test score of 69.73 increased to an average post-test score of 99.46. This improvement indicates that the learning activities effectively strengthened students’ understanding of green finance. In addition to the quantitative gains, students also produced creative and practical ideas for integrating green finance principles into daily school practices. This PKM contributes to the development of a practical and replicable model for integrating green financial literacy into vocational education. It is expected that the approach used in this program can serve as a sustainable learning model that supports the promotion of green finance awareness and environmentally conscious behavior among vocational school students.